Lags in Tax Collection–A Neglected Problem in War Finance - Hicks, Ursula K. (Review of Economic Studies, 1941)
Lags in Tax Collection—a Neglected Problem in War Finance Get access Ursula K. Hicks Ursula K. Hicks Prestbury Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 2, February 1941, Pages 89–99, https://doi.org/10.2307/2967465 Published: 01 February 1941